Ideology, Ideology-Critique, and the Critical Study of Religion in Bruce Lincoln’s Gods and Demons, Priests and Scholars: Critical Explorations in the History of Religions - Hewitt, Marsha Aileen (Bulletin for the study of religion, 2013)
This article is a review essay of Lincoln's latest book, contextualizing it within the general field of his previous work. The article situates Lincoln's work with respect to ideology critique mainly in the theoretical tradition of Marx and his critique of religion. It is argued that Lincoln's diagnosis of the current state of the study of religion remains captive to the current regulating practices deriving from some postmodern ideas, political correctness, and the hegemony of theology in 'religious' studies in the academy and its major professional association.